2020
DOI: 10.1590/0034-7167-2020-0421
|View full text |Cite
|
Sign up to set email alerts
|

Sarcopenia screening in elderly in primary health care: nurse knowledge and practices

Abstract: Objective: Describe the knowledge and practices of the Primary Health Care nurse on sarcopenia screening in the elderly. Methods: Qualitative study conducted with 24 Primary Health Care nurses. The data was collected through semi-structured interviews, recorded and later transcribed. The speeches were grouped in thematic categories, later analyzed, supported by Paulo Freire’s reference. Results: The findings showed that the primary care nurses’ knowledge of sarcopenia screening in the elderly was incipient a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 25 publications
(37 reference statements)
0
4
0
3
Order By: Relevance
“…A qualitative study by Silva et al, (2020) [ 28 ] highlighted the issue of a lack of knowledge among nurses in the primary care setting. It was further mentioned that, due to a lack of knowledge, the screening for sarcopenia is affected because the elderly at risk of developing the disease are not identified.…”
Section: Resultsmentioning
confidence: 99%
“…A qualitative study by Silva et al, (2020) [ 28 ] highlighted the issue of a lack of knowledge among nurses in the primary care setting. It was further mentioned that, due to a lack of knowledge, the screening for sarcopenia is affected because the elderly at risk of developing the disease are not identified.…”
Section: Resultsmentioning
confidence: 99%
“…Jackson et al [31] focused on the beneficial role of nurses through their awareness and interventions, such as screening for sarcopenia and offering appropriate education and treatment. Silva et al [32] supported the determinant role of primary care nurses in implementing promotional, preventive, and screening procedures for managing sarcopenia. However, their findings showed that nurses' knowledge of sarcopenia screening in the older population was incipient and fragile [32].…”
Section: Nurses and Early Screening Of Sarcopeniamentioning
confidence: 99%
“…Silva et al [32] supported the determinant role of primary care nurses in implementing promotional, preventive, and screening procedures for managing sarcopenia. However, their findings showed that nurses' knowledge of sarcopenia screening in the older population was incipient and fragile [32]. Özkaya Sağlam et al [33] emphasized the importance of nurses' role, as members of a multidisciplinary healthcare team, in preventing and early diagnosing sarcopenia and planning individual interventions.…”
Section: Nurses and Early Screening Of Sarcopeniamentioning
confidence: 99%
“…It is considered to be a main contributor to lower back pain (LBP), numbness and lower-limb dysfunction, which has become a serious medical problem and imposing a financial and health burden to the individual and society for its high morbidity [ 1 , 2 ]. Sarcopenia is an age-related disease that refers to the loss of muscle mass, strength and function, which may increase the risk of falls, fractures, and body dysfunction [ 3 5 ]. Currently, there are no approved therapies as the etiology of the two diseases are still not clearly defined.…”
Section: Introductionmentioning
confidence: 99%